1-(2-Hydroxyethyl)imidazolidine-2-thione - Lee, See Mun *; Ainnul H. S. Azizan, *; Tiekink, Edward R. T. * (MDPI, 2018)
1-(2-Hydroxyethyl)imidazolidine-2-thione (1) was obtained as a product from an in situ reaction between N-(2-hydroxyethyl)ethylenediamine, carbon disulfide, potassium hydroxide, and di(4-fluorobenzyl)tin dichloride. Compound 1 was characterized by IR, UV, 1H, 13C{1H}, and 2D (COSY, NOESY, HSQC, and HMBC) NMR spectroscopies. The cyclic molecular structure was confirmed by single crystal X-ray crystallography which showed the five-membered ring to be non-planar and the π-electron density to be localized over the CN2S chromophore. In the crystal, thioamide–N–H . . . O(hydroxy) and hydroxy–O–H . . . S(thione) hydrogen bonds lead to supramolecular layers in the bc-plane.